2023
DOI: 10.1080/0886022x.2023.2293224
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of thyroid hormone in CKD patients: a proof-of-concept of nephrogenic hypothyroidism

Rena Yuasa,
Masaki Muramatsu,
Akinobu Saito
et al.

Abstract: Purpose Patients with chronic kidney disease (CKD) complicated by hypothyroidism exhibit a higher prevalence of urine protein than that in the general population. This study was aimed at investigating thyroid hormones and thyroid hormone-binding proteins excreted in urine to elucidate the urine protein-associated underlying mechanisms of hypothyroidism. Methods Between November 2016 and August 2018, thyroid function (serum free T3 [sFT3], free T4 [sFT4], and thyroid-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has been indicated that CKD patients had higher levels of TSH, which was due to thyroid hormone loss in urine [ 30 ]. It was suggested that thyroid hormones and thyroid-binding proteins are wasted in the urine in CKD patients, leading to hypothyroidism [ 7 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been indicated that CKD patients had higher levels of TSH, which was due to thyroid hormone loss in urine [ 30 ]. It was suggested that thyroid hormones and thyroid-binding proteins are wasted in the urine in CKD patients, leading to hypothyroidism [ 7 ].…”
Section: Reviewmentioning
confidence: 99%
“…Thyroid dysfunction in CKD patients may be due to metabolic acidosis, malnutrition, chronic inflammation, and uremic toxins [ 5 ]. Moreover, the loss of thyroid hormones and thyroid-binding proteins in the urine may cause hypothyroidism [ 7 ]. In this narrative review, we searched the literature to find the complex interplay between thyroid hormones, thyroid dysfunctions, and chronic kidney diseases.…”
Section: Introductionmentioning
confidence: 99%